Supporting Women's Leadership Development in Global Health through Virtual Events and Near-Peer Networking. Issue 1 (7th January 2022) - Kalbarczyk, Anna; Harrison, Meagan; Chung, Eumihn; Glass, Nancy; Genberg, Becky; Decker, Michele R.; Manabe, Yukari C.
Women leaders have gained increasing attention during the COVID-19 pandemic for their positive influence on health and unique abilities to manage a global crisis, but women continue to face significant barriers to reaching and maintaining leadership positions. We developed a virtual leadership program to promote the experiences of women leaders in global health in different disciplines and career paths to develop concrete recommendations for young women and their institutions. This program includes a speaker series, interactive working groups, and a near-peer networking platform. In 2020, five global leaders spoke to over 1, 300 unique attendees representing 44 countries and shared their leadership experiences and key lessons learned. Leaders urged young women to take advantage of unexpected opportunities rather than follow discrete plans; build bridges with each other to foster diversity and inclusion; find their passions; and bolster 'essential skills' (i.e., communication and self-awareness). A brief online survey was circulated after each event. Seventy-nine percent of respondents (n = 158) agreed or strongly agreed that they have a greater understanding of solutions to combat challenges that women face in global health leadership and 54% (n = 107) of respondents reported that the event strengthened their network. The virtual approaches employed by this program in combination with the pandemic lockdown likely provided a unique opportunity to recruit high-level speakers and focus financial resources on communication and outreach. This type of programming can support a diverse cadre of women leaders including those with intersecting identities that are often marginalized or historically invisible in leadership ranks.